An Analysis of 2010 Senior High School National Examination Based on Bloom’S Taxonomy - Yulan M. Puluhulawa (ETERNAL (English Teaching Journal), 2015)
The main objective of this research was to find out the cognitive level of the 2010 Senior High School National Examination based on Bloom’s Taxonomy. The method used in this research is descriptive qualitative method. The result of the research showed that multiple choice test items that evaluate these higher levels of reasoning should present a case or situation to the student, and then require them to apply theories, processes, or other types of analysis learned in class to arrive at the answer to the multiple choice items based on the case information. In this test, the researcher viewed that the test was well constructed. In listening section, the native speaker is not as hard as others. Sometimes, the students are difficult to catch what speaker said. But, in this test, the conversation in the cassettes is not difficult to be grasped. After analyzing the test, the writer found that almost items are in Understanding Level. Except, the items number 4, 5 and 6. In this item, the students are required to classify or to match the pictures and the dialogue. In cognitive domain proposed by Blooms, matching pictures is in the first level.